Foreign Experience of Legal Support Privatization and the Possibility of its Use in Ukraine - Myroniuk, Roman Victorovich; Matviichuk, Anatolii; Hrabylnikova, Olena; Marchenko, Olesia (Jurnal Cita Hukum, 2021)
Successful examples of legal support privatization in a number of developed foreign countries are analyzed. In particular, the main attention was paid to the analysis of the experience of legal support privatization in developed and democratic countries of North America and Western Europe. The possibility and peculiarity of the procedure of introduction of specific forms and methods of legal support of the processes related to privatization in Ukraine are established. It is stated that privatization is one of the most significant phenomena both in the economy of a particular state and in society as a whole. It is noted that the proper legal enforcement and support of all privatization-related processes determine whether the economic development and prosperity of the state will take place, or, conversely, it will decline and suffer significant losses. It is noted that in connection with the gradual rapprochement of Ukraine with European states and their standards, the problem of inventing the most appropriate and relevant privatization of certain state or municipal enterprises is becoming more acute. At the same time, researchers prefer to conduct a qualitative analysis of the processes of privatization of state property that has taken place in the past in more detail, based on certain newly discovered facts. Among other things, it is considered necessary to check whether the rights, freedoms and legitimate interests of citizens, as well as the state, have been violated during the privatization process.Keywords: Privatization Legal Support; Implementation; Effective Activity; Qualitative Regulation; Research of Processes and PhenomenaPengalaman Asing Dalam Privatisasi Dukungan Hukum dan Peluang Penerapannya di Ukraina AbstrakContoh sukses privatisasi dukungan hukum di sejumlah negara maju asing dianalisis. Secara khusus, perhatian utama diberikan pada analisis pengalaman privatisasi dukungan hukum di negara-negara maju dan demokratis di Amerika Utara dan Eropa Barat. Kemungkinan dan kekhasan prosedur pengenalan bentuk khusus dan metode dukungan hukum dari proses yang terkait dengan privatisasi di Ukraina ditetapkan. Disebutkan bahwa privatisasi adalah salah satu fenomena paling signifikan baik dalam perekonomian suatu negara tertentu maupun dalam masyarakat secara keseluruhan. Penegakan hukum yang tepat dan dukungan dari semua proses terkait privatisasi menentukan apakah pembangunan ekonomi dan kemakmuran negara akan berlangsung, atau sebaliknya, akan menurun dan menderita kerugian yang signifikan. Sehubungan dengan pemulihan hubungan Ukraina secara bertahap dengan negara-negara Eropa dan standar mereka, masalah menciptakan privatisasi yang paling tepat dan relevan dari perusahaan negara bagian atau kota tertentu menjadi lebih akut. Pada saat yang sama, peneliti lebih memilih untuk melakukan analisis kualitatif terhadap proses privatisasi barang milik negara yang telah terjadi di masa lalu secara lebih rinci, berdasarkan fakta-fakta tertentu yang baru ditemukan. Antara lain, dipandang perlu untuk memeriksa apakah hak, kebebasan, dan kepentingan sah warga negara, serta negara, telah dilanggar selama proses privatisasi.Kata Kunci: Dukungan Hukum Privatisasi; Pelaksanaan; Kegiatan Efektif; Regulasi Kualitatif; Penelitian Proses dan Fenomena Зарубежный опыт правового обеспечения приватизации и возможность его использования в УкраинеАннотацияПроанализированы успешные примеры правового обеспечения приватизации в ряде развитых зарубежных стран. В частности, основное внимание было уделено анализу опыта правового обеспечения приватизации в развитых и демократических странах Северной Америки и Западной Европы. Установлены особенность процедуры введения конкретных форм и методов правового обеспечения процессов, связанных с приватизацией в Украине. Констатировано, что приватизация является одной из наиболее значимых явлений как в экономике конкретного государства, так и в обществе в целом. От надлежащего правового обеспечения и сопровождения всех связанных с приватизацией процессов зависит будет ли происходить экономическое развитие и процветание государства, или же наоборот она испытывает упадок и получит существенные убытки. В связи с постепенным приближением Украины к европейским государствам и их стандартов, все более остро встает проблема изобретение наиболее уместного и актуального проведения приватизации определенных государственных или коммунальных предприятий. Вместе с тем, исследователи предпочитают более детализировано, опираясь на определенные вновь открывшиеся факты, провести качественный анализ тех процессов приватизации государственной собственности, которые произошли в прошлом. Среди прочего, признается необходимым проверить, не были ли нарушены при проведении приватизации права, свободы и законные интересы граждан, а также интересы государства.Ключевые слова: приватизация, правовое обеспечение, эффективная деятельность, качественная регламентация, исследования процессов и явлений